Understanding Free Trade Attitudes: Evidence from Europe - Martin Braml; Gabriel Felbermayr (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Our paper contributes by demonstrating that public opinion on open-market policies is mainly shaped by ideology rather than by rational considerations and economic self-interest. Exploiting data on attitudes towards TTIP, Free Trade, Protectionism, and Globalization from the Eurobarometer, a comprehensive biannual survey across EU citizens, we find that individual preferences towards different trade policies can hardly be explained by variables that typically determine personal advantages of trade liberalization. Nevertheless, rational considerations follow expected patterns but are not overly relevant. Rather, we find trust variables and country-fixed-effects being predominant drivers of individual open-market attitudes. Our data also allow for a spatial analysis at the European NUTS-2 level. Performing a cross-country analysis, we find a causal relation between anti-Americanism and national TTIP approval rates. Macroeconomic performance variables contribute only to a minor extent in shaping regional and national preferences.
Keywords: F13; F53; F68; 330; International Political Economy; Free Trade Attitudes; TTIP